Corporation Social Responsibility and Bank Performance in Nigeria - Stephen Enughulu; Rebecca Omosefe Dabor (Faculty of Economics, Universitas Sriwijaya, 2018)
There have been divergent opinions by various scholars on the impact of corporate social responsibility activities on firm performance due to the upsurge costs involved in its provision. Some researchers maintained that it is the corporate entities’ obligation to recompense operating community for the destruction of its natural resources. This research work is aimed at ascertaining the connection of corporate social responsibility with performance of corporate entities. The sectorial scope of this study is the financial sector. Ten banks were chosen by randomization. The hypotheses were tested by panel least analysis method. The findings divulges that return on capital employed has no emblematic influence on CSR banks under review. The findings also showed a positive connection of return on investment with CSR banks under review. Lastly, the finding showed that the influence of net income margin on CSR is not emblematical.